Iniquidades sociossanitárias, práticas corporais e lugar social : um estudo em Vitória/es - Ciceri, Liliane Ferreira Sant’anna Bianchini (2015)
Although Vitória (ES) presents one of the largest accumulations of wealth production in the contemporary national scene, at the same time, you can verify the inside of your its city geography, the presence of a set of wicked socioeconomic contrasts that has persisted over the years. The existing framework of inequities found in intra-urban territories of this capital, suggests a relationship with to the implementation and maintenance of certain State policies of the county, instituting, since the 1990s, the supply of 'permanent equipment ' for the leisure body practices (PC), in public spaces, and 'considered' (by the public management) elements able to provide healthy practices to the population of this “capixaba “ city. From these premises, my research aimed to describe and analyze the geographical distribution of these devices (PC) along with the public safety equipment in two areas of Vitoria, selected for their notorious socio-sanitary disparities. I tried to verify that the comparative context of equipment allowed reveal connections with diverse socio-economic contexts of these two territories. The research, of a qualitative approach nature, used methodological elements of cartography, from which the findings of the study were situated and discussed their analytical inferences. The process of implementation of the work is expressed mainly in three steps described below: (1) preparation of systematic theoretical framework, not exhaustive, from the vast and dense conceptual contribution available on "inequities" and the "health- disease-care process "with a view to articulate the issues, and contextualize them as representative phenomena of paradoxical socio-economic and political reality of our country, in constant tension in the Brazilian State throughout its history; (2) survey, selection, organization and comparative analysis of secondary information regarding the presence and distribution of public facilities of PC, and geo-referenced public safety equipment in the state capital, later transformed into cartographic representations for the study; (3) return to the field, in two selected territories (Jardim da Penha, and Gurigica / São Benedito), to perform photographic records and notes in field diaries, with the aim of mapping, collate and reveal similarities and sociosanitary differences between the two "places" of the survey and also discuss these findings under the of cartographic representations of the analyzed equipment. The results of the study allow us to argue that, although there is some kind of public institutionalization of PC equipment in Victoria, lawyers as important elements in the context of population health by the public administration, on the other hand, the wicked geographic distribution of such equipment and what that means in terms of possibilities of access / popular use, can be correlated to socio- spatial segregation, the unfair inequalities and the undervaluation of certain places in the city, revealing element of existing inequities. Also significant differences were noted for the presence and spatial distribution of public safety equipment in both places of the research, which can interfere with the ability of people to do body practices.